ABOUT THE "INDUSTRIAL" POSTGRADUATE STUDIES (APPLIED RESEARCH) - B. I. Bednyi (Высшее образование в России)
The paper is a response to the article "Candidate Engineering - Academic Degree Required Now". The author focuses on the urgency of interaction between universities and enterprises in training highly qualified engineering personnel. The paper discusses the possible forms of such cooperation, the principles of organization of applied, industry-oriented targeted postgraduate programs.